Scoping Review: Pengaruh Kepatuhan Terapi Obat Anti Tuberkulosis terhadap Kesembuhan Pasien Tuberkulosis - Yunia Agustin; R.A Retno Ekowati; Zulmansyah (Bandung Conference Series: Medical Science, 2022)
Abstract. Tuberculosis (TB) is the second largest infectious disease in the world after HIV (Human Immunodeficiency Virus). TB treatment is carried out with Directly Observed Treatment Shortcourse (DOTS), namely direct supervision of taking medication. Patients are sometimes undisciplined in undergoing it so that the bacteria that cause TB are not completely removed from the body and only weakened which allows patients who have recovered to be reinfected (relapse). This study aims to determine the effect of adherence to anti-tuberculosis drug therapy on the healing of tuberculosis patients, using the Scoping Review method based on articles from the Pubmed, Garuda and Neliti databases with the keywords: a Cohort Study, Tuuberculosis adherence treatment, and tuberculosis treatment adherence from 2011 to 2021, It was found that 116 published articles met the inclusion criteria. After PICOS screening and eligibility, 5 (five) articles were obtained with the results of the review and analysis of each article using Univariate and Multivariate Regression Techniques stating that patient compliance resulted in a cure above 50%. In conclusion, TB patient recovery is influenced by the level of adherence of TB patients themselves, such as: supervision, education, family roles and dots. Abstrak. Tuberkulosis (TB) merupakan penyakit menular terbesar kedua di dunia setelah HIV (Human Immunodeficiency Virus). Pengobatan TB dilakukan dengan Directly Observed Treatment Shortcourse (DOTS), yaitu pengawasan langsung minum obat. Pasien terkadang tidak disiplin dalam menjalaninya sehingga bakteri penyebab TBC tidak sepenuhnya dikeluarkan dari tubuh dan hanya melemah yang memungkinkan pasien yang sudah sembuh dapat terinfeksi kembali (kambuh). Penelitian bertujuan untuk mengetahui pengaruh kepatuhan terapi obat anti tuberkulosis terhadap kesembuhan pasien tuberculosis, menggunakan metode Scoping Review berdasarkan artikel dari database Pubmed, Garuda dan Neliti dengan kata kunci : a Cohort Study, Tuuberculosis adherence treatment, dan kepatuhan pengobatan tuberkulosis dari tahun 2011 hingga 2021, ditemukan sebanyak 116 artikel yang diterbitkan memenuhi kriteria inklusi. Setelah skrining dan kelayakan secara PICOS, diperoleh 5 (lima) artikel dengan hasil telaah dan analisis pada setiap artikel dengan menggunakan Teknik Regresi Univariat dan Multivariat menyatakan bahwa kepatuhan pasien menghasilkan kesembuhan diatas 50%. Simpulan, kesembuhan pasien TB dipengaruhi oleh tingkat.